Kebijakan BPN Kota Tangerang Dalam Pembuatan Sertifikat Tanah - Eva Putra Jaya Zai; Dika Danuarta; Khikmawanto Khikmawanto (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Organizing government affairs in the land sector is The National Land Agency (BPN) holds the authority to manage land-related affairs, including the administrative resolution of land disputes within its jurisdiction.The foundation for BPN's ability to act as a mediator and assist the parties in identifying several options for settling conflicts without resorting to decision-making or coercion is Regulation of the Head of BPN No. 11 of 2016. To put it another way, this research approach combines qualitative legal data analysis with a normative legal research methodology. Land disputes that fall under BPN's purview are the focus of this study. A peace agreement signed by involving the disputing parties and the mediator, along with documented proceedings of the mediation process signed by the mediator, document the agreement achieved in the event that mediation is successful. The peace accord that the BPN mediator mediated is exclusively.